Geometrical analysis of planar coil design for fluxgate magnetometer - Yunas, Jumril; Sulaiman, Nadzril; Sugandi, Gandi; Hamzah, Azrul Azlan; Yeop Majlis, Burhanuddin (Springer Berlin / Heidelberg, 2010)
This paper presents geometrical analysis on the design of planar coupled coils for use as magnetic sensors. Inductance and magnetic coupling of the coil are analyzed using field solver analyzer ASITIC. Effects of different coil parameters, such as winding number, spacing, and width are discussed in detail. As results, the coil design considers not only the inductance value and the height of magnetic coupling, but also the geometrical area consumed. The analysis is verified by experimental data from coupled coil fabricated using surface micromachining techniques. An outer coil area having a typical dimension of 1.8 9 1.8 mm2 and a fix inner coil diameter of 500 lm was fabricated. Coupling factor of about 0.7 and self inductance of 12.7 nH were achieved, which show a reasonably good agreement with the simulated results. The coil platform developed offers an integrated solution for the design of fluxgate magnetometer.